How prophecy lives - Tumminia, Diana G.; Swatos, William H. (Religion and the social order 1061-5210, 2011)
5. Salvador Jimenez Murguia, When Prophets Fail to Fail: A Case Study of Yuko Chino, Chino Shoho, and the Pana-Wave Laboratory6. Lorne L. Dawson and Bradley C. Whitsel, Leadership and the Impact of Failed Prophecies on New Religious Movements: The Case of the Church Universal and Triumphant; 7. Stuart A. Wright and Arthur L. Greil, Failed Prophecy and Group Demise: The Case of Chen Tao; 8. Diana G. Tumminia, A Square Theory in a Round Reality: Thoughts on the Study of the Unarius Prophecy; William H. Swatos, Jr., Afterword: The Sociology of Prophecy Sub Specie Æternitatis; Contributors.